Insiders' Perspectives on the ACRL Framework for Information Literacy: An Interview with Trudi Jacobson and Craig Gibson - Lapointe, Jean-Michel (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2021)
This interview with the two U.S. librarians who co-chaired the Task Force that led to the creation of the Association of College & Research Libraries' Framework for Information Literacy for Higher Education (ACRL 2016) revisits the process of its creation as well as the reception this document has received five years after its inception. The authors retrace the main conceptual debates that have shaped the Framework and propose a typology of contemporary currents in information literacy, providing insight into the issues that inform the evolution of different conceptions of the pedagogical role of librarians in higher education from yesterday until today. This interview was translated into French.